IMPLETATION OF THE HOPE FAMILY PROGRAM (PKH) IN PROBIDING SOCIAL PROTECTION TO COMMUNITIES IN NAGAN RAYA DISTRICT - Meliya Sari (Jurnal Society : Pengamat Perubahan Sosial, 2023)
Based on an analysis of the implementation of the Family Hope Program (PKH) in providing social protection in Nagan Raya district. The Family Hope Program is a government program that provides direct cash assistance to people who meet the criteria. There are several factors in the implementation of the distribution of PKH benefit funds, both supporting factors and inhibiting factors. The Family Hope Program (PKH) is very useful in alleviating poverty as an effort to provide social protection in providing a good standard of living for the community in terms of clothing, food and shelter. Then there should be a final delivery of the data validation results to the participants concerned so that there are no misunderstandings between PKH beneficiaries and the village assistants. In this case there needs to be synergy between the Nagan Raya district social service and village officials in the distribution process, there needs to be understanding from related parties to have a positive impact on the benefits of PKH, so that the distribution process is not hampered so that the purpose of this PKH can provide social protection for the community aid beneficiaries.